Effect of food contamination and collection material in the measurement of biomarkers in saliva of horses. (April 2020) - Contreras-Aguilar, María Dolores; Hevia, María Luisa; Escribano, Damián; Lamy, Elsa; Tecles, Fernando; Cerón, Jose J.
Abstract: This study aims to evaluate the effect of the presence of food and the material used in a panel of biomarkers in saliva of horses. For the food effect study, clean saliva was incubated with a known amount of food consisting of oats, hay or grass. Significant changes were observed when saliva was incubated with oats for total protein ( P = .050) and phosphorus ( P = .008), with grass for total protein ( P = .037), salivary alpha-amylase (sAA, P = .018), total esterase (TEA, P = .018), butyrilcholinesterase (BChE, P = .037), adenosine deaminase (ADA, P = .037), and total bilirubin ( P = .018), and with hay for sAA ( P = .018), phosphorus ( P = .037), γ-glutamyl transferase (gGT, P = .004), and creatine kinase (CK, P = .016). For the material-based collection study, saliva using a sponge and a cotton role at the same time were collected and compared. Lower values were obtained in clean saliva collected with cotton role compared to sponge for sAA ( P = .030), TEA ( P = .034), BChE ( P = .003), gGT ( P = .002) and cortisol ( P < .001) In conclusion, the presence of food and the material used for its collection, can influence the results obtained when analytes are measured in saliva of horses. Highlights: The food in horse' saliva modifies the results for certain salivary biomarkers. Cotton role decrease the values of sAA, TEA, BChE, gGT and cortisol. The same material for saliva sampling must be employed during all the experiment.